« Хорошо где нас нет »L’émigration des « Russophones » d’Asie centrale - Julien Thorez (EchoGéo)
The present article deals with the emigration of Russian speaking population from Central Asia after the collapse of the Soviet Union. It aims to analyze the determining factors of the post-soviet mobility (economic crisis, civil war, interethnic relations) and to put this process into the recent history of migrations. In so doing, this paper explores the repercussions of this massive flow on Central Asia, which represents a fundamental aspect of the post-soviet transformation.